Estimation of leaf area in turmeric (Curcuma longa L.) under two agroecological conditions - A RAMADASAN, K V SATHEESAN, M V GEORGE, K VIJAYAKUMAR (Journal of Spices and Aromatic Crops, 1994)
The total leaf area (TLA) at different stages of growth of tillers or clumps of turmeric (Curcuma longa) varieties raised under two agroecological conditions viz., in the open as a pure crop and in association with coconut, can be estimated using the regression equation TLA = bl nB + b2 L. The total leaf area of the tiller or clump can be computed by taking the linear measurements (’L’ and ’B’) of only one leaf i.e., median leaf of the tiller or those of the median leaf of the tiller having maximum number ofleaves, respectively, and counting the total number of leaves (’n’) in the respective tiller or clump. Under both the ecological conditions studied and between the same, the regression coefficients were not homogenous over various stages of growth and for different varieties. Hence common mathematical formulae were not attempted to, with regard to varieties, age of the plant or ecological conditions.